GROWTH AND FEED CONVERSION RATIO OF OREOCROMIS NILOTICUS FEEDED MAGGOT AND NATURAL INGREDIENTS IN CULTIVATION BASED ON BUDIKDAMRUM TECHNOLOGY - Budiyati Budiyati; Ardana Kurniaji; Diana Putri Renitasari; Yunarty Yunarty; Anton Anton (Politeknik Kelautan dan Perikanan Dumai, 2023)
Tilapia fish Oreochromis niloticus is one type of freshwater fish that is widely cultivated by farmers. Cultivation of tilapia in drums (budikdamrum) has the potential to be carried out on limited land by feeding maggot. This research was conducted to evaluate the feeding of maggot (Hermetia illucens) combined with natural ingredients on the growth and feed conversion ratio of tilapia based on budikdamrum technology. The study was carried out with 2 treatments, namely DP (fish fed with maggot 10 g/day + natural ingredients in the form of Moringa leaf flour (Moringa oleifera), garlic flour (Allium sativum), tapioca flour), and DK (fish fed pellets of 10% biomass/day without natural ingredients). Kale plants were grown in 5 cups filled with foam and activated carbon mounted on the top of the drum. Fish were kept for 25 days, and sampling was done every 3 days. The results showed that the growth of tilapia in DK was higher than DP (P<0.05). Specific growth of fish weight 6.01±0.13 – 7.13±0.04% and length 1.90±0.06 – 2.42±0.32 cm. absolute growth of fish weight 4.67±0.03 – 6.62±0.89 g and length 2.85±0.10 – 3.73±0.44 cm. The feed conversion ratio did not show any difference between DP and DK (P>0.05), namely 1.26±0.08 – 1.38±0.19. The survival rate of tilapia treated with DP was higher than DK (P<0.05) with a range of 89±4.90 - 98±2.83%. The water quality obtained in this study was included in the category of requirements for tilapia cultivation. The application of the budikdamrum technology is recommended for rearing tilapia with maggot feed as additional feed mixed with natural ingredients.